Partisipasi Masyarakat dalam Pembentukan Undang-undang - Author: Saifudin (Jurnal Hukum IUS QUIA IUSTUM, 2003)
it is not something strange to find that a constitution of law validated in the society is rejected by any element of society in implementing it because the material content is unmatched with societal interest and it is far from the societal justice, even it tends to elitist. Therefore, it need to think on the process of societal participation in creating the constitution on laws.